POLICY REFORMS IN ENERGY SECTOR RETHINKING NEOLIBERALISM IN A WELFARE STATE (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2013)
This paper is intended on searching of liberalization development process particularly in the energy sector reflected by policy changes in Indonesia. It examines and investigates to what extend policy changes in Indonesia coherent with neo-liberalism characters particularly after Asian Crisis in 1997 which followed by Suharto’s regime resignation, when liberalization process was heavily accelerated by reformed government. The problem that rose next was how neoliberalism thoughts may convergence into welfare state ideology as the founding fathers ideas accordingly. The conclusion part clearly discusses about the pros and cons of neo-liberalism characters in policy changes in Indonesia.